Merianthera calyptrata sp. nov. (Melastomataceae, Myrtales), a new candelabriform species from Minas Gerais, Brazil - Goldenberg, Renato; Bochorny, Thuane; Amorim, André Márcio; Ziemmer, Juliana Klostermann; de Fraga, Claudio Nicoletti (European Journal of Taxonomy, 2023)
Merianthera is a genus of flowering plants with up to now seven species occurring in eastern Brazil, in the states of Bahia, Espírito Santo, and Minas Gerais. It belongs to the tribe Pyramieae (Melastomataceae), and can be recognized by its shrubby or treelet habit with caducous leaves, 5-merous flowers with a strongly zygomorphic androecium, the latter with dimorphic stamens bearing complex dorsal connective appendages, as well as an inferior ovary and capsular fruits. We describe here a new species of Merianthera from two collections and a photographic record, all from the same locality, an inselberg in the Municipality of Jacinto, in northeastern Minas Gerais. Its candelabriform habit, with a fistulose stem, and solitary, axillary or cauliflorous flowers are only shared with M. burlemarxii. However, M. calyptrata R.Goldenb., Bochorny & Fraga sp. nov. has at least three characters that are absent in M. burlemarxii and all other species in the genus: the total absence of both a peduncle and bracteoles, the calyptrate calyx and the fruits developing from inferior ovaries and dehiscing through longitudinal slits. The first character appears to be unknown in other species in the family.